Metabolomic and transcriptomic insights into the mechanism of sugar and acid accumulation in the pulp of sour- and sweet-tasting Baccaurea ramiflora Lour. - Huang, Jianjian; Chen, Jie; Zhu, Yingchun; Wen, Xueying; Deng, Kangyi; Lin, Xiuxuan; Zhu, Hui; Zheng, Yuzhong; Wu, Qinghan; Zheng, Yongqin; Wu, Fengnian; Yong, Jean Wan Hong (Frontiers in Plant Science, 2025)
IntroductionThe taste differences between sour-tasting (LR) and sweet-tasting (BR) fruits of Baccaurea ramiflora Lour. are pronounced, but the underlying molecular mechanisms remain unclear.MethodsThis study employed a combined metabolomic and transcriptomic analysis to elucidate the metabolic pathways governing this flavour variation.ResultsMetabolomic profiling identified D-(+)-glucose and citric acid as the key taste determinants, with BR fruits exhibiting a significantly higher sugar-to-acid ratio than LR fruits. Transcriptomic data revealed that invertase (INV) activity correlated with D-glucose levels, whereas sucrose synthase (SUS) and sucrose-phosphate synthase (SPS) were associated with sucrose accumulation. In fully mature BR fruits, the suppressed expression of INV suggested that reduced sucrose hydrolysis contributes to their enhanced sweetness. Conversely, in LR fruits, elevated expression of hexokinase (HK) indicated higher glucose utilization. Furthermore, the expression of genes involved in organic acid metabolism—including citrate synthase (CS), aconitase (ACO), and NADP-malic enzyme (NADP-ME)—was found to regulate the content of citric and malic acids.DiscussionThese findings advance our understanding of the molecular basis of flavour formation in B. ramiflora, and provide potential targets for the breeding and biotechnological improvement of fruit taste.